APPLYING DUOLINGO APPLICATION TO IMPROVE YOUNG LEARNERS’ ENGLISH VOCABULARY: STUDENTS’ PERCEPTION IN INDONESIA - Marinda, Midha Ayu (Journal of English Teaching and Learning, 2025)
This study aims to find out the perceptions of young students about using the Duolingo application to increase their English vocabulary. The subjects or respondents in this study were students in one of the elementary schools in Banyuwangi, totaling 17 students. The method used in this research is qualitative. Data collection procedures using questionnaires and interviews. Researchers chose 17 students to collect data through a questionnaire. Based on the results of the questionnaire statements number 1 to 17 students gave positive statements aboutYoung learners' perceptions of the Duolingo application because the results of the combined form data strongly agree (5) and agree (4) show results of more than 50%. Researchers chose 10 students to collect data through interviews. The results of the interview analysis of 10 participants showed that their perception of the Duolingo application for learning English was very positive. Each stated that the Duolingo app was useful to them. Most of the participants stated that the Duolingo application was very fun and easy to use as a medium for learning English vocabulary for young learners. Some students like speaking and story tasks in the Duolingo application. Based on the research results with data through questionnaires and interviews, it shows that young learners agree that the Duolingo application can add to their vocabulary.